2010
DOI: 10.1523/jneurosci.0329-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking CD11b-Positive Blood Cells Deliver Therapeutic Genes to the Brain of Amyloid-Depositing Transgenic Mice

Abstract: A major question for gene therapy in brain concerns methods to administer therapeutic genes in a uniform manner over major portions of the brain. A second question in neuroimmunology concerns the extent to which monocytes migrate to the CNS in degenerative disorders. Here we show that CD11bϩ cells (largely monocytes) isolated from the bone marrow of GFP (green fluorescent protein)-expressing donors spontaneously home to compacted amyloid plaques in the brain. Injections of these cells as a single pulse show a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
123
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(134 citation statements)
references
References 39 publications
9
123
1
1
Order By: Relevance
“…Blood-borne monocytes have been shown to infiltrate damaged or diseased brain tissue in animal models of other human neurological disease, such as the EAE model of multiple sclerosis (35), Alzheimer's disease (27,28,44), and traumatic brain injury (13,45). Previous studies have also reported elevated numbers of peripheral immune leukocytes after epileptiform activity (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Blood-borne monocytes have been shown to infiltrate damaged or diseased brain tissue in animal models of other human neurological disease, such as the EAE model of multiple sclerosis (35), Alzheimer's disease (27,28,44), and traumatic brain injury (13,45). Previous studies have also reported elevated numbers of peripheral immune leukocytes after epileptiform activity (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…This is relevant for myeloid cell-based gene therapy in AD. In fact, infusion of millions of genetically engineered BM-derived CD11b ϩ cells into APP swe/PS1 transgenic mice resulted in some parenchymal myeloid cell engraftment and modulation of amyloid deposition (Lebson et al, 2010). The impact of gene therapeutic approaches using myeloid precursors for CNS diseases has been highlighted in a mouse model of metachromatic leukodystrophy (Biffi et al, 2004), and more recently, in children with X-linked adrenoleukodystrophy (Cartier et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in AD mouse models, bone marrow-derived macrophages have been shown to limit plaque growth (45) and genetically modified monocytes can modulate AD pathology (46). Importantly, microglial apoptosis has been implicated in X-linked adrenoleukodystrophy (ALD) (21), and beneficial clinical outcomes have been reported in ALD patients subject to therapies using nonmutant myeloid cells (47).…”
Section: Discussionmentioning
confidence: 99%